PERANCANGAN SISTEM INFORMASI PENDAFTARAN PASIEN BERBASIS WEB : STUDI KASUS PUSKESMAS PURNAMA DUMAI - Azmi, Khairul; Urva, Gellysa; Sari, Aulia (Jurnal Komputer dan Teknologi, 2025)
This study aims to design a web-based patient registration information system at Puskesmas Purnama, Dumai City, to address the inefficiencies of the existing manual registration process. The conventional method often leads to long queues, data entry errors, and delayed services. The system was developed using the Waterfall model, consisting of requirement analysis, system design, implementation, and testing phases. The application was built using PHP for programming and MySQL as the database, with a web interface designed to be user-friendly for both staff and patients. The resulting prototype allows online registration and provides a more structured and efficient data management process. With this system, the administrative services at Puskesmas Purnama are expected to become faster, more accurate, and digitally integrated.